(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This paper explores the emergence and representation of the "New Woman" through the protagonists of two culturally distinct novels: Caroline Meeber in Theodore Dreiser’s Sister Carrie and Nilufar in Zulfiya Qurolboy qizi’s Oyimtilla. By comparing these characters, the study highlights how female identity, agency, and aspirations are shaped within differing socio-cultural and historical contexts—turn-of-the-century industrial America and post-independence Uzbekistan. Through a comparative literary analysis, the research investigates the characters’ psychological development, their resistance to traditional gender norms, and the extent to which they embody the concept of the "New Woman." The paper aims to demonstrate how both authors portray women navigating societal expectations while seeking personal autonomy, thereby enriching the literary discourse on women’s evolving roles in modern society.